The Drosophila model for microbiome research. (June 2018) - Douglas, Angela
Abstract The gut microbiome is increasingly recognized to play an important role in shaping the health and fitness of animals, including humans.Drosophila is emerging as a valuable model for microbiome research, combining genetic and genomic resources with simple protocols to manipulate the microbiome, such that microbiologically sterile flies and flies bearing a standardized microbiota can readily be produced in large numbers. StudyingDrosophila has the potential to increase our understanding of how the microbiome influences host traits, and allows opportunities for hypothesis testing of microbial impacts on human health.Drosophila is being used to investigate aspects of host-microbe interactions, including the metabolism, the immune system and behavior.Drosophila offers a valuable alternative to rodent and other mammalian models of microbiome research for fundamental discovery of microbiome function, enabling improved research cost effectiveness and benefits for animal welfare. Angela Douglas reviews the use ofDrosophila melanogaster as a model organism in microbiome studies.